Empirical analysis of Six Sigma project capability deficiency and its impact on project success. Issue 3 (8th May 2019) - Hudnurkar, Manoj; Ambekar, Suhas; Bhattacharya, Sonali
Abstract : Purpose: The purpose of this paper is to understand the deficiencies in Six Sigma project capability and empirically validating its impact on project success. Design/methodology/approach: Deficiencies are identified from literature focusing on Six Sigma challenges or barriers. The study used a survey approach by circulating questionnaires to 400 Six Sigma professionals from 40 multinational organisations. The conceptual model is composed of 16 items measuring five constructs for hypothesis testing. Furthermore, structural equation modelling was used to identify the relationship between Six Sigma project capability deficiency and project success. Findings: The findings of the study suggest that inadequate top management support, inadequate resources and change management and inadequate quality maturity form Six Sigma project capability deficiency and affect project success. Research limitations/implications: The study uses resource-based view to understand the deficiencies in Six Sigma project capability and their impact on project success. The study confirms that organisational capabilities in implementing Six Sigma affect the success of the projects. Practical implications: The results of this study reveal that inadequate top management support, inadequate quality maturity of the organisation and inadequate resources and change management result into a deficiency in Six Sigma project capability. Quality managers in manufacturing and service organisations should attempt to improve these capabilities to achieve competitive advantage. Originality/value: The study contributes to the literature by exploring the capability outlook of Six Sigma. The study attempts to fill the gap in Six Sigma literature by providing a structural model for understanding Six Sigma project capability deficiency and its impact on Six Sigma project success.